Designing a Sport Development Model in Iran's Free Trade Industrial Zones - Amin Saberi; Masoumeh Kalateh Seifari; Morteza Dosti; Seyed Mohammad Hossin Razavi; Farzam Farzan (The Society of Aging and Physical Activity (SAPA), 2018)
Background. One of the most important elements of life are physical activity and sport: these are the basis of health during life. In order for society to benefit from the advantages of physical activity and sport, it is necessary to know the factors influencing this phenomenon. Objectives. The purpose of this paper is to design a sport development model in the free trade-industrial zones of Iran. Methods. The research was qualitative, and was done using the grounded theory approach and based on the systematic approach of Strauss and Corbin (1998). The geographic area of the research included seven free trade trade-industrial zones of Iran; the data collection tool was a semi-structured interview. Participants in the research were the sport authorities of Iran's free zone, sport officers, officers of the Ministry of Sport and Youth of free zones, staff members of the Ministry of Sports and Youth, and sports professors; interviews involved 22 informed persons. Results. The results of data coding showed that causal factors (individual, interpersonal, and structural) centrally affect sport development. Cultural, social, economic, political, technological, legal, and environmental factors were also selected as context and interventional factors. Development of management; development of space, equipment, and great sports events; cultural and social development; scientific and legal development; and development of financial resources were designated as strategies for the development of sport, which will also lead to economic, cultural, social, environmental, and political consequences. Conclusion. Given the positive outcomes for the development of sport, it can be useful as an effective tool in achieving the major goals of Iran's free trade-industrial zones.